The influence of spatial configuration on pedestrian movement behaviour in commercial streets of low-density cities - Elham Mehrinejad Khotbehsara; Kathirgamalingam Somasundaraswaran; Tracy Kolbe-Alexander; Rongrong Yu (Ain Shams Engineering Journal)
This research investigates the interplay of spatial arrangement and pedestrian behaviour in Toowoomba City Centre, a low-density city in Australia, using a combination of quantitative and qualitative analysis through Space Syntax. In contrast to high-density and medium-density areas where street connectivity typically drives movement patterns, this study emphasises the significant roles of both syntactical factors and land-use mapping in low-density contexts. The study identifies a correlation between pedestrian activity and land-use mapping and compatibility in low-density areas, advocating for strategic land-use planning within a 150–320-metre radius. It demonstrates that while traditional syntactic metrics are relevant, pedestrian movement in low-density areas is more significantly influenced by land-use diversity and compatibility during daytime hours (1–3 PM). Both syntactical factors and land-use are also crucial for attracting pedestrians during evening and night hours (6–8 PM). These findings highlight the importance of place-making strategies to foster vibrant, pedestrian-friendly environments.